2014
DOI: 10.1175/jas-d-13-076.1
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and Equilibration of Jets in Beta-Plane Turbulence: Applications of Stochastic Structural Stability Theory

Abstract: Stochastic Structural Stability Theory (S3T) provides analytical methods for understanding the emergence and equilibration of jets from the turbulence in planetary atmospheres based on the dynamics of the statistical mean state of the turbulence closed at second order. Predictions for formation and equilibration of turbulent jets made using S3T are critically compared with results of simulations made using the associated quasi-linear and nonlinear models. S3T predicts the observed bifurcation behavior associat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
104
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(111 citation statements)
references
References 51 publications
7
104
0
Order By: Relevance
“…In geophysical fluid dynamics, zonal jets or zonal flows occur when the velocity field is aligned with latitude circles, and they depend only on the longitude coordinate y, i.e., = U y v e ( ) x . Furthermore, multiple zonal jet configurations were observed as dynamical attractors in the quasi-geostrophic model for the same set of parameters [36]. These examples provide the necessary motivation to try to understand rare transitions between two attractors for geophysical fluid flows.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…In geophysical fluid dynamics, zonal jets or zonal flows occur when the velocity field is aligned with latitude circles, and they depend only on the longitude coordinate y, i.e., = U y v e ( ) x . Furthermore, multiple zonal jet configurations were observed as dynamical attractors in the quasi-geostrophic model for the same set of parameters [36]. These examples provide the necessary motivation to try to understand rare transitions between two attractors for geophysical fluid flows.…”
mentioning
confidence: 76%
“…However, it must be stated that this is only an approximate measure because the structure of the noise correlation will also contribute. Moreover, many cases of multiple steady-state solutions of the barotropic equation with differing numbers of jets have been observed for the same sets of parameters [36]. These multiple states are assumed to be linearly stable for the unforced (with or without dissipation) dynamics.…”
Section: Dynamics Of the Statistically Steady Statementioning
confidence: 99%
“…Stochastically forced models were also utilized in the context of stochastic structural stability theory to study jet formation and equilibration in barotropic beta-plane turbulence (Farrell & Ioannou 2003Bakas & Ioannou 2011;Constantinou et al 2014a;Bakas & Ioannou 2014). Recently, it was demonstrated that a feedback interconnection of the streamwise-constant NS equations with a stochastically-driven streamwisevarying linearized model can generate self-sustained turbulence in Couette and Poiseuille flows (Farrell & Ioannou 2012;Thomas et al 2014;Constantinou et al 2014b).…”
Section: Stochastic Forcing and Flow Statisticsmentioning
confidence: 99%
“…While there are several studies which show the utility of the quasi-linear approximation (e.g. Srinivasan & Young 2012;Constantinou, Farrell & Iouannou 2014) and while this approximation would certainly be valid in some parameter regimes (as per our scalings in ε early in the paper), we recognise that the approach may principally be useful as a qualitative rather than quantitative guide to behaviour in full nonlinear simulations. We have also assumed scale separation between waves and mean flows, and this can be relaxed by using the correlation function formulation developed by Srinivasan & Young (2012) and discussed by Bakas & Iouannou (2013).…”
Section: Discussionmentioning
confidence: 86%
“…What is neglected is the interactions of waves giving smaller-scale waves, in other words the beginning of a turbulent cascade. In the context of zonostrophic instability, these ideas and applications are developed in the stochastic structural stability theory of Farrell & Iouannou (2003, Bakas & Iouannou (2011 and Constantinou, Farrell & Iouannou (2014). Here coupled equations for mean flow and waves, with additional stochastic forcing, are solved numerically in a variety of systems, showing robust jet formation, and the quasi-linear theory validated against direct simulations.…”
Section: Introductionmentioning
confidence: 99%